The roles of lncRNA functions and regulatory mechanisms in the diagnosis and treatment of hepatocellular carcinoma - Hong, Yuling; Zhang, Yunxing; Zhao, Haibo; Chen, Hailing; Yu, Qing-Qing; Cui, Hongxia (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) is the most frequent and deadly type of liver cancer. While the underlying molecular mechanisms are poorly understood, it is documented that lncRNAs may play key roles. Many HCC-associated lncRNAs have been linked to HBV and HCV infection, mediating gene expression, cell growth, development, and death. Studying the regulatory mechanisms and biological functions of HCC-related lncRNAs will assist our understanding of HCC pathogenesis as well as its diagnosis and management. Here, we address the potential of dysregulated lncRNAs in HCC as diagnostic and therapeutic biomarkers, and we evaluate the oncogenic or tumor-suppressive properties of these lncRNAs.